Physical, structural and mechanical properties of wollastonite-based foam glass ceramics using eggshell and soda-lime-silica glass waste - Saparuddin, Dur Iffa (2020)
Foam glass-ceramics represents a highly valuable solution for lightweight fill material, which has a low density, incombustible, and good in mechanical strength. In this work, foam glass-ceramics were prepared by the solid-state conventional method, using soda-lime-silica (SLS) glass waste as a matrix glass and eggshell (ES) as a foaming agent. The purpose of this study is to synthesize and study the changes that occur in physical, structural, and mechanical properties of foam glass-ceramic derived from waste materials by varying the ES content, sintering temperature, and sintering duration. Both of the raw materials were milled and sieved to the particle size of 45 μm. The powders then were homogenized with the empirical formula, [ES]x[SLS]100-x where x = 1, 3, 6, and 9 wt.%. and uniaxially pressed with 5 MPa. The obtained compact powders were heat-treated at 700, 800, and 900 °C for 30, 60, and 120 min with the constant heating rate at 10 °C/min. The foam-glass ceramic samples were then analyzed based on physical properties; measured by density, linear expansion, and porosity. The structural properties of the foam glass-ceramic samples were determined by X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Fourier Transform Infrared Spectroscopy (FTIR). Then, the mechanical properties of the sample were measured using Universal Testing Machine (UTM). The optimum parameter of the foam glassceramics was obtained at 800 °C for 60 min with the substitution of 3 to 6 wt.% ES content. In fact, the optimum temperature was supported by the thermogravimetric analyzer (TGA) which indicates that the mass loss of CaCO3 in ES occurs at the temperature of 800 °C. The samples prepared this way to provide a minimum bulk density of 0.326 – 0.421 g/cm3 with the maximum porosity of 87.2 – 83.16 %. Furthermore, XRD analysis revealed that the formation and growth of cristobalite (SiO2) and wollastonite (CaSiO3) crystal phases after the heat-treatment process at 800 °C. Meanwhile, the FTIR analysis indicates the strong intensity of Ca‒O bond at 620 to 650 cm‒1 of wavenumber associate with decreasing the intensity peak of C‒O after the heat-treatment process at 800 °C. FESEM analysis showed that the pores are larger and abundant distributed with the size of the diameter’s pore is 861 – 1200 μm in the samples with 3 to 6 wt.% of ES content. The results of compressive strength for the sample with 3 and 6 wt.% ES content increases from 0.04 and 0.42 MPa, respectively, depending on the crystalline phase content. Therefore, 6 wt.% ES is an appropriate ratio for fabricating foam glass-ceramics with a low density and high compressive strength. The preparation of foam glass-ceramics using solid wastes provide a promising way to prepare ceramic aggregate for the construction application as well as giving benefit to the economy and environment issue.